Advances in MicroRNA-Mediated Reprogramming Technology - Chih-Hao Kuo; Shao-Yao Ying (Hindawi Limited, 2012)
The use of somatic cells to generate induced-pluripotent stem cells (iPSCs), which have gene characteristic resembling those of human embryonic stem cells (hESCs), has opened up a new avenue to produce patient-specific stem cells for regenerative medicine. MicroRNAs (miRNAs) have gained much attention over the past few years due to their pivotal role in many biological activites, including metabolism, host immunity, and cancer. Soon after the discovery of embryonic-stem-cell- (ESC-) specific miRNAs, researchers began to investigate their functions in embryonic development and differentiation, as well as their potential roles in somatic cell reprogramming (SCR). Several approaches for ESC-specific miRNA-mediated reprogramming have been developed using cancer and somatic cells to generate ESC-like cells with similarity to iPSCs and/or hESCs. However, the use of virus-integration to introduce reprogramming factors limits future clinical applications. This paper discusses the possible underlying mechanism for miRNA-mediated somatic cell reprogramming and the approaches used by different groups to induce iPSCs with miRNAs.